Construction and Characterization of a Triple-Recombinant Vaccinia Virus Encoding B7-1, Interleukin 12, and a Model Tumor Antigen - Carroll, Miles W. (1998)
BACKGROUND: Construction of recombinant viruses that can serve as vaccines for the treatment of experimental murine tumors has recently been achieved. The cooperative effects of immune system modulators, including cytokines such as interleukin 12 (IL-12) and costimulatory molecules such as B7-1, may be necessary for activation of cytotoxic T lymphocytes. Thus, we have explored the feasibility and the efficacy of inclusion of these immunomodulatory molecules in recombinant virus vaccines in an experimental antitumor model in mice that uses Escherichia coli β-galactosidase as a target antigen. METHODS: We developed a “cassette” system in which three loci of the vaccinia virus genome were used for homologous recombination. A variety of recombinant vaccinia viruses were constructed, including one virus, vB7/β/IL-12, that contains the following five transgenes: murine B7-1, murine IL-12 subunit p35, murine IL-12 subunit p40, E. coli lacZ (encodes β-galactosidase, the model antigen), and E. coli gpt (xanthine-guanine phosphoribosyltransferase, a selection gene). The effects of the recombinant viruses on lung metastases and survival were tested in animals that had been given an intravenous injection of β-galactosidase-expressing murine colon carcinoma cells 3 days before they received the recombinant virus by intravenous inoculation. RESULTS: Expression of functional B7-1 and IL-12 by virally infected cells was demonstrated in vitro. Lung tumor nodules (i.e., metastases) were reduced in mice by more than 95% after treatment with the virus vB7/β/IL-12; a further reduction in lung tumor nodules was observed when exogenous IL-12 was also given. Greatest survival of tumor-bearing mice was observed in those treated with viruses encoding β-galactosidase and B7-1 plus exogenous IL-12. CONCLUSION: This study shows the feasibility of constructing vaccinia viruses that express tumor antigens and multiple immune cofactors to create unique immunologic microenvironments that can modulate immune responses to cancer.